Women and irrigation in Nepal: Context, issues and prospects - Ghimire, Sujan (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 2,025 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v9i0.1140 Occasional Papers in Sociology and Anthropology Vol.9 2005 p.176-193